Pelatihan Meningkatkan Kualitas SDM dan Soft Skills di Yayasan Pendidikan Islam Tajaul Karomatu Kabupaten Tangerang - Shella Puspita Sari; Endang Puji Astutik; Abdullah Abdullah (Jurnal PKM Manajemen Bisnis, 2026)
Human resources and soft skills are critical components for the improvement of educational institutions. At Yayasan Pendidikan Islam Tajaul Karomatu in Tangerang Regency, there is a need to enhance the competencies of teachers, staff, and student leaders to support the quality of education. This community service program (PKM) aimed to improve the quality of human resources and soft skills of the school members. The PKM was carried out on October 5, 2025, by six lecturers from Universitas Pamulang, involving 24 participants consisting of teachers, school staff, and OSIS members. The program was conducted in three stages: preparation, implementation, and reporting. The implementation involved a combination of methods, including material presentation, practical exercises, discussion, and question-and-answer sessions. The results showed that participants significantly increased their understanding and application of effective communication, teamwork, leadership, and problem-solving skills. Participants also reported enhanced confidence in performing their professional and organizational duties. Furthermore, the interactive methods encouraged active engagement, allowing participants to immediately practice the skills learned. This PKM demonstrated that structured training programs could effectively improve both technical competencies and interpersonal skills, contributing to the overall development of the school community. The collaboration between universities and schools provides a sustainable model for human resource development in educational institutions.